Numerical solution of non-Newtonian fluid flow and heat transfer problems in ducts with sharp corners by the modified method of fundamental solutions and radial basis function collocation. (December 2019) - Grabski, Jakub Krzysztof
Abstract: In this paper, non-Newtonian fluid flow and heat transfer in an internally finned duct is considered. The problems are governed by nonlinear equations with linear boundary conditions. In this paper, the solution is obtained with two Picard iteration processes, separately for the fluid flow and heat transfer problems. Furthermore, in both problems the solutions consist of the general and particular solutions. The method of fundamental solutions is employed in order to obtain the general solution while radial basis function approximations are used for obtaining the general solution by two possible methods. The results obtained using both approaches give similar results.